(untitled) (Journal of Engineering, 2020)
Highly plastic soils exhibit unfavorited properties upon saturation, which produce different defects in engineering structures. Attempts were made by researchers to proffer solutions to these defects by experimenting in practical ways. This included various materials that could possibly improve the soil engineering properties and reduce environmental hazards. This paper investigates the strength behavior of highly plastic clay stabilized with brick dust. The brick dust contents were 10%, 20%, and 30% by dry weight of soil. A series of linear shrinkage and unconfined compression tests were carried out to study the effect of brick dust on the quantitative amount of shrinkage experienced by highly plastic clay and the undrained shear strength. The effect of curing on soil shear strength was included in this paper. It was found that the critical behavior of highly plastic soil can be mitigated by mixing with 20% or 30% of brick dust. The undrained shear strength of highly plastic clay mixed with brick dust increased with the increase of brick dust content up to 20%. It was affected by the curing period. The best improvement was achieved when the optimum content of brick dust was 20%. Finally, seven days of curing improved the undrained shear strength with over 100%.